Heat stress-induced photosynthetic impairment and autophagy modulation in Paris polyphylla var. yunnanensis: A physiological and molecular Perspective - Lixia Lin; Xueqin Zhang; Ruiyun Lai; Jianzhong Lin; Zanhua Zhong; Huihua Li (PLoS ONE, 2026)
High temperature is one of the major environmental stressors that severely affects plant growth. Paris polyphylla var. yunnanensis , a traditional Chinese herbal medicine, is sensitive to high temperature. However, the underlying mechanisms of its response to high temperature remain unclear. In this study, we investigated the physiological and proteomic change of P. polyphylla var. yunnanensis under different treatments (25°C, 30°C, 35°C, 40°C). Our results showed that high temperature directly impaired photosynthesis and disrupted metabolism, evidenced by reduced chlorophyll and photosynthetic rate, as well as accumulated proline and increased conductivity. A total of 893 differentially expressed proteins (DEPs) were identified, with significant changes in the expression levels of enzymes associated with protein processing and synthesis. Additionally, the expression levels of key proteins involved in the circadian pathway and the glutathione pathway were also notably upregulated. Dynamic changes in the endocytosis and autophagy-related proteins ATG3 and ATG8C were also observed, suggesting that these processes may play a significant protective role under high-temperature stress. Overall, this study provides an important starting point for improving the heat tolerance of P.polyphylla var. yunnanensis through genetic engineering.